School-Based Inclusive Education Management as a Quality Assurance System in Indonesia (Systematic Literature Review) - Riowati Riowati; Wiwin Hendriani; Pramesti Paramita (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study aims to provide an understanding and description of the success of school-based inclusive education management to improve the quality of inclusive education at every level of education in Indonesia. This study uses a systematic literature review method with the PRISMA method. Data were collected by reviewing the official websites of Sciencedirect, Researchgate, Sinta, and Garuda. The data search process uses inclusive educators, quality of education, inclusive education problems, and school-based inclusive education management. The data obtained were then analyzed to understand school-based inclusive education management studies using thematic techniques to identify the pattern of a study. The results of the study showed that the concept of school-based inclusive education management can be a solution to the problems of inclusive schools at every level in improving the quality of education by optimizing the role of educational components such as teachers as the main resource in managing the system to evaluating the learning process in modified curriculum, facilities, and infrastructure. Findings from research results such as (1) Schools should make programs based on the needs and culture of the school, (2) The role of teachers is important in realizing quality education, (3) School-based inclusive management is a reference for other schools to develop creative and innovative educational programs in responding to the challenges of inclusive education.